Fatty Acids Metabolism: The Bridge Between Ferroptosis and Ionizing Radiation - Yuan, Zhu-hui; Liu, Tong; Wang, Hao; Xue, Li-xiang; Wang, Jun-jie (Frontiers in Cell and Developmental Biology, 2021)
Exposure of tumor cells to ionizing radiation (IR) alters the microenvironment, particularly the fatty acid (FA) profile and activity. Moreover, abnormal FA metabolism, either catabolism or anabolism, is essential for synthesizing biological membranes and delivering molecular signals to induce ferroptotic cell death. The current review focuses on the bistable regulation characteristics of FA metabolism and explains how FA catabolism and anabolism pathway crosstalk harmonize different ionizing radiation-regulated ferroptosis responses, resulting in pivotal cell fate decisions. In summary, targeting key molecules involved in lipid metabolism and ferroptosis may amplify the tumor response to IR.